How to achieve the global 90‐90‐90 target by 2020 in sub‐Saharan Africa? A mathematical modelling study. Issue 11 (19th September 2018) - Estill, Janne; Marsh, Kimberly; Autenrieth, Christine; Ford, Nathan
Summary: Objectives: The 90‐90‐90 target states that by 2020, 90% of people living with HIV should be diagnosed, 90% of those diagnosed treated, and 90% of those treated virally suppressed. We assessed the actions needed in each country of sub‐Saharan Africa to achieve the 90‐90‐90 target. Methods: We developed a mathematical model to assess the number of patients needing to start antiretroviral therapy (ART) between 2017 and 2020 to achieve 81% coverage by 2020 in each country, and the proportion of treated patients who are virally suppressed in four scenarios, combining two scenarios of retention (current‐level or perfect), and routine viral load monitoring (current or universal coverage). We performed two separate simulations, one using observed failure rates from cohort studies, and one with considerably lower failure rates to set a theoretical lower limit. Results: Our model projected that 2.9 million people started ART in 2017 in sub‐Saharan Africa. If, depending on scenario, at least 2.2–2.7 million patients continue to start ART annually, 81% ART coverage will be reached in 2020 in sub‐Saharan Africa on average. In 37% of the countries, a multiple‐fold increase in annual number of patients starting ART is needed. Virological suppression >90% in 2020 could be reached only in the best‐case scenario assuming low probability of treatment failure, elimination of treatment interruptions, and universal routine viral load monitoring. Conclusion: The 90‐90‐90 target is realistic in sub‐Saharan Africa on average, but not necessarily in all individual countries. Each country should identify and focus on the specific gaps needing attention.